Dzielimy się doświadczeniemThe assessment of left and right ventricular function in patients with severe pulmonary diseases - Nowak, Jolanta; Kukulski, Tomasz; Zębik, Tadeusz; Rozentryt, Piotr; Jastrzębski, Dariusz; Wojarski, Jacek; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
In patients with pulmonary diseases, the assessment of heart morphology and function is very important for further pharmacological and surgical treatment and rehabilitation. Pulmonary diseases, especially with pulmonary hypertension, often lead to right ventricular failure. This article presents many aspects of right ventricular dysfunction in patients with severe pulmonary diseases. We briefly describe the anatomy, physiology and pathophysiology of the right ventricle. The most useful diagnostic methods to detect right ventricular failure are discussed. We focus on echocardiography as a simple, readily available in most institutions, a non-invasive and inexpensive method. Echocardiography with the great number of classical and new parameters is still a basic and efficient screening tool of morphology and function of cardiac structure in patients with severe pulmonary diseases.